2017
DOI: 10.1007/s10964-017-0713-5
|View full text |Cite
|
Sign up to set email alerts
|

And What About Siblings? A Longitudinal Analysis of Sibling Effects on Youth’s Intergroup Attitudes

Abstract: Within the process of political socialization, the family is of particular importance. Apart from parents, however, little is known about the role of other close family members. The present study examined if siblings affect each other's intergroup attitudes (i.e., intolerance towards immigrants, social dominance orientation). Drawing on a sample of 362 sibling dyads (older siblings: M = 17.77, 53.6% female; younger siblings: M = 13.61, 61.3% female), the results showed that older siblings' intergroup attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…The social learning perspective model (SLPM; Bandura, 1992) posits that relative to family guardians (e.g., parents), older siblings have a greater potentially positive impact on the language development of younger children because of their close age and generational experience (Eckstein et al, 2018; Spector & Charlop, 2018). Older siblings also serve as sources of a language learning model for younger children during their preschool years (Eckstein et al, 2018; Milevsky, 2016; Obied, 2009). For example, Eckstein et al (2018) showed that younger sisters showed a significantly better performance in their vocabulary after a learning interaction with their older siblings.…”
Section: Language Learning In Adhd Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…The social learning perspective model (SLPM; Bandura, 1992) posits that relative to family guardians (e.g., parents), older siblings have a greater potentially positive impact on the language development of younger children because of their close age and generational experience (Eckstein et al, 2018; Spector & Charlop, 2018). Older siblings also serve as sources of a language learning model for younger children during their preschool years (Eckstein et al, 2018; Milevsky, 2016; Obied, 2009). For example, Eckstein et al (2018) showed that younger sisters showed a significantly better performance in their vocabulary after a learning interaction with their older siblings.…”
Section: Language Learning In Adhd Childrenmentioning
confidence: 99%
“…Older siblings also serve as sources of a language learning model for younger children during their preschool years (Eckstein et al, 2018; Milevsky, 2016; Obied, 2009). For example, Eckstein et al (2018) showed that younger sisters showed a significantly better performance in their vocabulary after a learning interaction with their older siblings. Empirical research has supported the use of older siblings–instructional interventions in enhancing the receptive vocabulary development of younger children (e.g., Shivers & Plavnick, 2015).…”
Section: Language Learning In Adhd Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a systematic review reported that sibling influences depended on siblings’ frequent and emotional intense interactions and siblings’ role in large family system dynamics (McHale et al, 2012). Considering age ranking, recent adolescence literature has confirmed the psychological interactions between older siblings and younger siblings during adolescence with increasing age (e.g., Eckstein et al, 2018; Wang M.T. et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Of the many factors that shape young people's political development, experiences in proximal contexts, such as home, school, or the peer group, have gained particular attention (Neundorf and Smets, 2017). Research has shown that young people encounter politics at school (Miklikowska et al, 2019;Noack and Eckstein, 2023) and adopt political attitudes from parents (Miklikowska, 2016;Legget-James et al, 2023) or other family members (Eckstein et al, 2018). Yet, in line with contextual models of human development (Bronfenbrenner, 1979), more distal macro-contexts such as societal events (e.g., wars, political upheavals, scandals) also play a role.…”
Section: Introductionmentioning
confidence: 99%